2017
DOI: 10.1590/0074-02760170145
|View full text |Cite
|
Sign up to set email alerts
|

Culex quinquefasciatus from areas with the highest incidence of microcephaly associated with Zika virus infections in the Northeast Region of Brazil are refractory to the virus

Abstract: Zika virus (ZIKV) is widely distributed in Brazil and the Northeast Region (NE) is the most affected zone, showing the highest incidence of microcephaly associated with ZIKV congenital infections worldwide. We report attempts to infect three populations of Culex quinquefasciatus from severely affected sites in the NE and Southeast Region (SE) of Brazil with three strains of ZIKV isolated from these localities. An Aedes aegypti population from the SE was used as a positive control. All tested Cx. quinquefasciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…quinquefasciatus confirm that these mosquitoes are not competent for ZIKV transmission. Using field-collected Culex mosquitoes and ZIKV strains isolated from patients in the northeast region of Brazil as performed by Guedes et al [38], Fernandes et al [61] showed that Cx. quinquefasciatus populations were not competent for transmitting the virus.…”
mentioning
confidence: 99%
“…quinquefasciatus confirm that these mosquitoes are not competent for ZIKV transmission. Using field-collected Culex mosquitoes and ZIKV strains isolated from patients in the northeast region of Brazil as performed by Guedes et al [38], Fernandes et al [61] showed that Cx. quinquefasciatus populations were not competent for transmitting the virus.…”
mentioning
confidence: 99%
“…quinquefasciatus for ZIKV in China. In contrast, several other studies have demonstrated the lack of ability of this mosquito to infect and transmit ZIKV (4648). These results confirm that the vector competence of the same mosquito species can vary geographically, emphasizing the importance of studying the vector competence of different mosquitoes and from different localities.…”
Section: Discussionmentioning
confidence: 79%
“…Seven studies found that Cx. quinquefasciatus mosquitoes were refractory to Zika virus when exposed to infectious blood meals [128,134139]. Ferreira-de-Brito et al [129] reported that no Cx.…”
Section: Resultsmentioning
confidence: 99%